Efektivitas Pengelolaan Petty Cash dan Perannya dalam Mendukung Operasional Harian di PT Zee Indonesia - Talitha Nabilah; Gina Sakinah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effectiveness of petty cash management at PT Zee Indonesia and its role in supporting the company's daily operations. This study uses a descriptive method with a qualitative approach through observation and interviews with the finance department as the primary data sources. The results show that petty cash is used for routine needs such as transportation, consumption, purchasing stationery, and business travel, with a multi-layered approval mechanism by finance staff, managers, and commissioners. The implemented system is considered a fluctuating system, as the petty cash balance can be increased according to operational needs. Although management has been running well, obstacles such as late claims and discrepancies in recording are still encountered. The conclusion of this study indicates that petty cash management at PT Zee Indonesia has been effective but requires more consistent control to maintain accountability and reliability of financial reports. The novelty of this study lies in the implementation of the petty cash system in a hybrid work environment (WFH and WFO), and the results are expected to serve as a reference for research and practical accounting learning in the field of internal control.